Empresa Ciam Beef “Análisis De Mercado País Para Los Productos Cárnicos De La Empresa Ciam Beef (2022)
Determine Objectives of the internship the viability of exporting fine cuts of BEEF meat, from the factors of: logistic, operational and Administrative advice of the CIAM company; in order to identify potential markets in the 1.2.2 Specific objectives  abroad